Notes on the genus Messageria Bavay & Dautzenberg, 1904, with descriptions of a new species and a new subspecies (Gastropoda: Caenogastropoda: Cyclophoroidea: Alycaeidae) - Chen, Zhe-Yu; Lin, Li-Wen (Zootaxa, 2021)
In this study, the systematic status of Messageria Bavay & Dautzenberg, 1904 is discussed. It is recognized as an alycaeid genus, rather than as a subgenus or a junior synonym of Helicomorpha Möllendorff, 1890 (Diplommatinidae) as previously thought. Additionally, a new species, Messageria sinica n. sp. from Guizhou, and a new subspecies, Messageria scalarioides donghiana n. ssp. from Guangxi are described. Messageria scalarioides donghiana n. ssp. is morphologically different from the nominate subspecies by the larger shell and wider lower whorls and umbilicus. Messageria sinica n. sp. is morphologically different from the type species by having larger shell and distinct intermediate ribs.